2009
DOI: 10.1007/s11102-009-0207-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of self- or partner-administration of an extended-release aqueous-gel formulation of lanreotide in lanreotide-naïve patients with acromegaly

Abstract: Surgical resection is often not curative in patients with acromegaly and long-acting somatostatin analogues (lanreotide or octreotide) are often needed. This study assessed the efficacy and safety of self- or partner-administration of lanreotide in patients with acromegaly. This was a six-month, single-arm, open-label study conducted at 13 endocrinology clinics. Fifty-nine patients received deep subcutaneous lanreotide injections every 28 days. Twelve patients started on 120 mg lanreotide and forty-seven start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 14 publications
3
67
1
2
Order By: Relevance
“…Previous studies of self- or partner administration of SSA in patients with acromegaly report that patients are able and willing to self- or partner inject (12, 13, 14, 15), which is in complete contrast to this study and to the authors’ own clinical experience. The differences in patients’ attitudes might be explained by the patients’ younger age and shorter length of treatment with SSA in the previous studies compared with this study (12, 13, 14, 15).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Previous studies of self- or partner administration of SSA in patients with acromegaly report that patients are able and willing to self- or partner inject (12, 13, 14, 15), which is in complete contrast to this study and to the authors’ own clinical experience. The differences in patients’ attitudes might be explained by the patients’ younger age and shorter length of treatment with SSA in the previous studies compared with this study (12, 13, 14, 15).…”
Section: Discussioncontrasting
confidence: 90%
“…Because lanreotide autogel is supplied in prefilled syringes and is injected into deep subcutaneous tissue, it is possible for patients with acromegaly to use self- or partner-administered injection (11), and this offers the possibility to lead a more independent life. Further, injections of lanreotide have been shown to be given reliably and safely outside a health care clinic and are considered as an alternative to injections by health care professionals for motivated patients (12, 13, 14, 15). In the study by Salvatori and coworkers, the primary end-point of which was to evaluate the efficacy and safety of self- or partner administration, 70% of the participants were able to self-inject and 30% to partner inject correctly after training (13).…”
Section: Introductionmentioning
confidence: 99%
“…Octreotide long-acting release (LAR) is administered once monthly by intramuscular injection; lanreotide autogel is administered once monthly subcutaneously by the patient, their caregiver or a health-care provider. As efficacy rates are similar for the two agents 19,60 , preference for route of delivery and/or associated cost might influence treatment choice 63 (VLQ). Studies have shown that higher doses of octreotide LAR (60 mg every 28 days) as well as higher doses (180 mg every 28 days) and more frequent dosing (120 mg every 21 days) of lanreotide autogel can improve biochemical control rates in patients who are inadequately controlled on standard doses but are responsive to SRL therapy 64,65 (MQ).…”
Section: Somatostatin Receptor Ligandsmentioning
confidence: 99%
“…This figure is lower than those reported in previous guidelines and published papers that might have had patient selection bias due to the stringent inclusion and exclusion criteria required for clinical trials (MQ). 6,18,24 Long-term (>3 years) results on the efficacy and safety profile of SRLs are reassuring (HQ), 18,25,26 and lowering the SRL dose or decreasing the frequency of administration of SRLs might be considered for patients with long-term control of acromegaly (VLQ). 27 When reducing the SRL dose or decreasing the frequency of administration, patients should be reassessed at regular intervals to ensure maintenance of therapeutic effect (SR).…”
Section: Somatostatin Receptor Ligandsmentioning
confidence: 99%
“…18,28 However, lanreotide and octreotide differ in their mode of administration (long-acting lanreotide formulations are available in ready-to-use prefilled syringes that are injected subcutaneously; long-acting octreotide formulations require reconstitution before being injected intramuscularly), which might influence patient convenience (VLQ). 24 At least two other SRL formulations are currently undergoing clinical development for acromegaly: pasireotide, which has a different somatostatin receptor-binding profile; 29 and oral octreotide. 30 …”
Section: Somatostatin Receptor Ligandsmentioning
confidence: 99%